Comparative Antioxidant, Phytochemical and Proximate Analysis of Aqueous and Methanolic Extracts of Vernonia amygdalina and Talinum triangulare - Anyasor, God`swill Nduka; Ogunwenmo, Kayode Olusola; Ogunnowo, Adewale Ayodele; Alao-Sanni, Olabisi (Pakistan Journal of Nutrition, 2010)
This study evaluated and compared in vitro antioxidant activity, phytochemical constituent and proximate analysis of aqueous and methanolic leaf extracts of Vernonia amygdalina and Talinum triangulare to determine their acceptability in folkloric medicine. The total phenolic content of aqueous and methanolic extracts of V. amygdalina (0.822±0.050 and 0.681±0.050 mg gallic acid equivalent GAE/g respectively) was higher than aqueous and methanolic extract of T. triangulare (0.456±0.040 and 0.288±0.020 mg GAE/g respectively). Furthermore, DPPH scavenging activity of V. amygdalina was significantly higher (p<0.05) than T. triangulare at all levels of concentration (100, 200 and 300 μg/ml). Lipid peroxidation was inhibited by all samples, although there was no significant difference (p>0.05). Aqueous extracts of leaf tested positive to tannin, phlobatannins, cardiac glycosides, saponins, phenols, flavonoids and alkaloids. The proximate composition of V. amygdalina leaf showed higher percentage crude fibre, fat, protein and total carbohydrate content than T. triangulare except moisture and ash contents. Methanolic and aqueous leaf extracts of V. amygdalina possess higher antioxidant properties, phyto-nutrients and longer shelf life than T. triangulare and hence it’s pervading use and acceptability in folkloric and trado-medicine.